Concrete beams with different arrangements of GFRP flexural and shear reinforcement. (1st November 2019) - Krall, M.; Polak, M.A.
Highlights: Deep beams showed concrete controlled shear failure with arching action. Shear strength increases with longitudinal and shear reinforcement ratios. Shear stirrups increase post peak deformability, generally. Shear reinforcement provides decreasing returns as more is added to the span. Stirrups have negligible impact on concrete contribution to shear strength. Abstract: This paper presents experimental research on the flexural and shear behaviour of concrete beams reinforced with glass fibre reinforced polymer (GFRP) composite reinforcement. Three-point bending tests on shear critical concrete beams reinforced with GFRP longitudinal bars and GFRP stirrups are presented. The test variables were the size and spacing of closed loop stirrups as well as the size, amount, and arrangement of longitudinal reinforcement. Twelve beams were tested with four different stirrup arrangements and three different longitudinal reinforcement arrangements. Longitudinal bars were instrumented at mid-span and stirrups were instrumented at the straight and bent portions. The beams had a shear-span-to-effective-depth ratio of 2.5 and behaved like deep beams. The beams without stirrups failed in shear-tension while the beams with stirrups failed in shear-compression with no ruptured stirrups. Longitudinal reinforcement strains showed evidence of a tied arch mechanism. The analysis found diminishing increases in shear strength with increasing shear reinforcement ratio when failure occurred as a result of crushing of confined concrete.